Chronic Kidney Disease and Arterial Stiffness: A Two-Way Path - Inserra, Felipe; Forcada, Pedro; Castellaro, Agustina; Castellaro, Carlos (Frontiers in Medicine, 2021)
The kidney-heart relationship has raised interest for the medical population since its vast and complex interaction significantly impacts health. Chronic kidney disease (CKD) generates changes in the vascular structure and function, with significant hemodynamic effects. In addition, the arterial stiffening resulting from vascular inflammation and oxidative stress induces changes and deterioration in the left ventricular function and alteration in tissue perfusion. CKD amplifies the inflammatory cascade's activation and is responsible for altering the endothelium function, increasing the vascular tone, wall thickening, and favors calcium deposits in the arterial wall. Simultaneously, the autonomic imbalance and alteration in other hormonal systems also favoring the overactivation of inflammatory and fibrotic mediators and participates in arterial dysfunction and its structural alteration through all the vascular wall layers. On the other hand, a rise in arterial stiffening and volume overload generates high left ventricular afterload. It increases the left ventricular burden with consequent myocardial remodeling, development of left ventricular hypertrophy, and, in turn, heart failure. It is noteworthy that reduction in glomerular mass of renal diseases generates a compensatory glomerular filtration overdriven associated with large-arteries stiffness and high cardiovascular events. Furthermore, we consider that the consequent alterations of the arterial system's mechanical properties are crucial for altering tissue perfusion, mainly in low resistance. Thus, increasing the knowledge of these processes may help the reader integrate them from a pathophysiological perspective, providing a comprehensive idea of this two-way path between arterial stiffness and renal dysfunction and their impact at the cardiovascular level.